The motivation and its importance in the teaching-learning process - Alcivar, Carmen Magdalena Mero; Quimi, Tatiana Lizeth Ibarra; Barberan, María Fernanda Zambrano (International research journal of management, IT and social sciences, 2020)
This article aims to analyze the motivation and importance in the teaching-learning process for students and the teacher and how the interrelation of meaningful learning between the teacher who imparts knowledge-generating stimulate their classes and students who are capable to explore, investigate, learn new skills through the motivation provided by the educational setting. The qualitative research describes theoretical content, guided by the deductive-inductive method referenced from journals, bibliographies, and analytical-descriptive. It has, as a result, the motivation in students, techniques and methodological strategies to achieve their goals.